Facial Recognition Based Attendance System for Santai Esports (FRASE) - AHMAD ZAMRE, SHAHRUL SYAZWAN; ZAINAL, NUREZAYANA (Applied Information Technology And Computer Science, 2025)
Santai Esports in Taman Universiti faces operational hurdles with just two staff members relying on a rotating shift system. Planning to expand, the informal method compromises accuracy and complicates payroll. The proposed solution is a user-friendly Facial Recognition Attendance System, aiming to automate tracking and enhance security. The system, including modules for registration and analytics, targets efficient attendance tracking, reduced workload, and staff accountability. Implemented with the structured Waterfall model, it positions Santai Esports for market growth, addressing inefficiencies and establishing a foundation for robust staff management. The Facial Recognition Attendance System aims to enhance efficiency, accuracy, and overall success.